2016
DOI: 10.1590/1679-78253010
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Instability of Beams Under Tip Follower Forces Using Geometrically Exact, Fully Intrinsic Equations

Abstract: In this study, the dynamic instability of beams under tip follower forces are considered. The beam is modeled by using the geometrically exact, fully intrinsic beam equations which is subjected to an inclined tip follower force. Generalized differential quadrature method is employed to solve the governing equations. The effect of different parameters such as follower force inclination and magnitude, rotating speed, the distance between the beam center of gravity and elastic center, and cross-sectional properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The overall dynamics of the composite hingeless rotor blade is simulated by the geometrically exact fully intrinsic beam equations [30], which has been used successfully to model beam-like structures [31][32][33][34][35]. These equations…”
Section: Formulationmentioning
confidence: 99%
“…The overall dynamics of the composite hingeless rotor blade is simulated by the geometrically exact fully intrinsic beam equations [30], which has been used successfully to model beam-like structures [31][32][33][34][35]. These equations…”
Section: Formulationmentioning
confidence: 99%
“…They found that the GDQ method can obtain more accurate results with a lesser computational cost than the traditional finite element method. Based on GDQ method, they also analyzed the dynamic stability of the beam under following forces [30] and the aeroelastic stability of the hingeless rotor [31]. Tashaorian et al [16] used the GDQ method for the spatial discretization of non-local fully intrinsic equations.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of cantilever beams subjected to uniformly distributed non-conservatives was investigated by Fazelzadeh and Kazemi-Lari [5]. Amoozgar and Shahverdi [6] studied the effect of non-conservative forces on the dynamic stability of isotropic blades using exact beam theory. They showed that the blade rotating speed and direction of the force significantly change the dynamic behavior of the blade.…”
Section: Introductionmentioning
confidence: 99%